Design of a multi-echelon supply chain network with transportation mode selection and outsourcing opportunities - Cortinhal, M. J.; Lopes, M. J.; Melo, M. T. (International Symposium On Locational Decisions (ISOLDE) XIV, 2017)
We address the problem of designing a multi-echelon logistics network motivated by a cement company. Strategic decisions comprise opening new facilities and selecting their capacities from a set of available discrete sizes. In addition, logistics decisions are also to be made and involve supplier selection, procurement, production, and distribution of multiple products. The latter also include the choice of transportation modes having limited capacities. Finally, a strategic choice between in-house manufacturing and a mixed approach with product outsourcing is to be taken. We propose a mixed-integer linear programming (MILP) formulation and develop additional inequalities to enhance the original formulation.Moreover, we also consider the special situation in which all products delivered to customers must be in-house manufactured.In contrast to most of the literature on supply chain design, in this case, customer demands may be partially satisfied under the condition that a minimum service level is achieved. To gain insight into how challenging the problems at hand are to solve, a computational study is performed with randomly generated instances and using a general-purpose solver. Useful insights are derived from analyzing the impact of different business strategies on various segments of the supply chain network.